Dark data capitalisation behaviour of Muslim micro enterprises in the context of issues, challenges, and best practices in Malaysia. - Marzuki, Nur Athifah Syairah; Md Ajis, Ahmad Fuzi; Ahmad, Abdul Rahman; Mokhtar, Rashidah (Journal of Islamic, Social, Economics and Development, 2025)
Data management in business is crucial regardless of the business size, including Muslim micro enterprises. Properly managed data becomes an asset to the business. In contrast, data that is stored but not actively managed or utilised is classified as hidden data, or unused data, or dark data. This study aims to explore the issues, challenges, and best practices related to dark data management among Muslim micro enterprises. It also investigates the process of transforming unused data (dark data) into meaningful information that supports decision-making, enhances operations, or creates new business opportunities, referred to as dark data capitalisation. The study adopts an interview approach to examine the practices of Muslim micro enterprises in managing dark data. The findings of this study identify the key issues, challenges, current practices and best practices associated with dark data capitalisation among Muslim micro enterprises. The findings significantly important to the micro enterprise for the growth. Future research may lead to the development of guidelines or a management model for dark data capitalisation, helping Muslim micro enterprises generate added value for their operations, strategies, and growth.